Molecular Cloning and Expression of a Phytase Gene from the Thermophilic Fungus, Thermomyces lanuginosus - RMB - Palanivelu*, Sowmiya Balasubramanian; Peramachi (Journal of Phytology, 2011)
Phytases are enzymes which hydrolyse phytate to produce inorganic phosphate and myo-inositol and thus they are promising candidates for food and feed industries. Thermomyces lanuginosus is known to produce a thermostable phytase. In this work, the Thermomyces lanuginosus strain RMB was chosen for cloning and expression of the phytase gene. Intronless primers were designed for phytase gene amplification and expression in E. coli, using the phytase gene sequence of T. lanuginosus (ATCC 200065). A product of 1400 bp characteristic of phytase gene was obtained on PCR amplification of the fungal genomic DNA. This gene was cloned into pGEM-T easy vector and the positive clones were confirmed by restriction digestion and sequenced. The cloned gene obtained in this study will have a potential for producing the thermostable enzyme in large amounts, which could find applications in the feed industry to enhance the quality for poultry and piggery by supplementing it in their diets.